2019
DOI: 10.1111/apt.15330
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: efficacy of faecal microbiota transplantation for the treatment of irritable bowel syndrome

Abstract: Summary Background Increasing evidence supports the role of the gut microbiota in the aetiology of irritable bowel syndrome (IBS). Faecal microbiota transplantation (FMT) is a highly effective treatment against recurrent Clostridioides difficile infection in randomised controlled trials (RCTs), and may be beneficial in ulcerative colitis. However, its efficacy in IBS is uncertain. Aim To perform a systematic review and meta‐analysis to examine this issue. Methods We searched MEDLINE, EMBASE, EMBASE Classic, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
145
1
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(160 citation statements)
references
References 51 publications
(139 reference statements)
4
145
1
10
Order By: Relevance
“…After a thorough search of published studies investigating the association between H pylori eradication and oesophageal adenocarcinoma incidence in PubMed, Embase and Web of Science database, only three related studies were identified including that by Kumar et al (Table 1). 1,7,8 Overall, the incidence of oesophageal adenocarcinoma after H pylori eradication was 0.01%-0.07% and there was no significantly increased risk of oesophageal adenocarcinoma following eradication. Perhaps the initial belief that H pylori protected against oesophageal adenocarcinoma through gastric acidity impairment seems to be a bias and is rather unlikely.…”
Section: Ack N Owled G Em Entsmentioning
confidence: 96%
“…After a thorough search of published studies investigating the association between H pylori eradication and oesophageal adenocarcinoma incidence in PubMed, Embase and Web of Science database, only three related studies were identified including that by Kumar et al (Table 1). 1,7,8 Overall, the incidence of oesophageal adenocarcinoma after H pylori eradication was 0.01%-0.07% and there was no significantly increased risk of oesophageal adenocarcinoma following eradication. Perhaps the initial belief that H pylori protected against oesophageal adenocarcinoma through gastric acidity impairment seems to be a bias and is rather unlikely.…”
Section: Ack N Owled G Em Entsmentioning
confidence: 96%
“…Fecal microbiota transplantation FMT is defined as the transmission of the gut microbiome derived from healthy donors to unhealthy recipients through the digestive tract route, which aims to reestablish gut homeostasis or to provide a new balance in order to abrogate or ameliorate 482 FMT has been recognized as a standard treatment for recurrent CDI by official guidelines with a nearly 90% cure rate. 482,483 Researchers are also increasingly realizing the potential of FMT in other noncancerous diseases, such as IBD, [484][485][486] IBS, 487 liver disease, 488 and neuropsychiatric disorders. 489 Hence, knowledge obtained from FMT in these diseases is also emerging evidence to indicate that FMT can be potentially employed in the management of cancer.…”
Section: Microbiome-mediated Effects On Cancer Immunotherapymentioning
confidence: 99%
“…Numerous studies have confirmed its efficacy and superiority to antibiotics in recurrent CDI. New research suggests that because of its effect on the microbiome, it may even have a role in other systemic diseases including inflammatory bowel disease, irritable bowel syndrome, and hepatic encephalopathy . As a relatively new option, FMT use remains limited to primarily academic centers and protocols are often facility dependent .…”
Section: Introductionmentioning
confidence: 99%